2011
DOI: 10.1187/cbe.11-02-0013
|View full text |Cite
|
Sign up to set email alerts
|

Improving Graduate Education to Support a Branching Career Pipeline: Recommendations Based on a Survey of Doctoral Students in the Basic Biomedical Sciences

Abstract: Today's doctoral programs continue to prepare students for a traditional academic career path despite the inadequate supply of research-focused faculty positions. We advocate for a broader doctoral curriculum that prepares trainees for a wide range of science-related career paths. In support of this argument, we describe data from our survey of doctoral students in the basic biomedical sciences at University of California, San Francisco (UCSF). Midway through graduate training, UCSF students are already consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
329
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 252 publications
(351 citation statements)
references
References 16 publications
22
329
0
Order By: Relevance
“…A graduate education in the sciences produces individuals with broadly applicable skills in critical thinking and problem-solving, whose expertise could be invaluable in fields such as science policy and administration, the commerce of science, science writing, the law, and science education at all levels. Furthermore, recent surveys reveal that a substantial fraction of today's graduate students in the sciences are interested in pursuing nonresearch careers (13,14). However, for the most part, neither the faculty nor the students are well enough informed about such careers.…”
Section: Bringing the Biomedical Enterprise Intomentioning
confidence: 99%
“…A graduate education in the sciences produces individuals with broadly applicable skills in critical thinking and problem-solving, whose expertise could be invaluable in fields such as science policy and administration, the commerce of science, science writing, the law, and science education at all levels. Furthermore, recent surveys reveal that a substantial fraction of today's graduate students in the sciences are interested in pursuing nonresearch careers (13,14). However, for the most part, neither the faculty nor the students are well enough informed about such careers.…”
Section: Bringing the Biomedical Enterprise Intomentioning
confidence: 99%
“…Concerning DRE, we were able to identify two PCs [student writes and submits manuscripts to journals, and student participates or presents at conferences and seminars] that significantly predict productivity. These results provide empirical support for the efficacy of practices that focus on intensive technical writing activities [39,45] and of having doctoral students actively engage in the publication process early in their training [38]. For the students we surveyed, this meant producing papers even before writing their own dissertation.…”
Section: Discussionmentioning
confidence: 55%
“…As such, we labeled this component "Mentor helps students with actual bench work." From these results, we observed that mentoring practices in our survey sites were not only confined to research advising, guidance, and helping hone analytical and technical skills [38]. Instead, they also included experience in co-directing projects (research management), co-authoring papers, and receiving help in the job search [42][43][44].…”
Section: Doctoral Mentoring Practicesmentioning
confidence: 82%
“…Importantly, the creation of mentored teaching opportunities for our senior graduate students and postdoctoral fellows was meaningful not only for their scientific development [17] but also to allow them a professional development opportunity in education that is not as readily available on a medical campus as it might be on an undergraduate campus. The importance of professional development opportunities outside of experimental science has become increasingly essential as the diversity of students' professional goals has come to light [18,19].…”
Section: Box 3bmentioning
confidence: 99%